2011 IEEE International Conference on Robotics and Automation 2011
DOI: 10.1109/icra.2011.5979988
|View full text |Cite
|
Sign up to set email alerts
|

On the use of shunt impedances versus bounded environment passivity for teleoperation systems

Abstract: This paper analyses and compares two passivitybased approaches that allow to include a-priori knowledge on the dynamic range of the human operator and/or the environment. This can lead to less conservative teleoperation systems compared to systems designed to be purely passive or absolutely stable. The first approach under investigation is a method where the absolute stability is analysed of a teleoperation system augmented with shunt impedances in series and/or parallel with the teleoperation system. It is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Although Willaert et al (2011) and Tosun and Patoglu (2020) showed that higher physical damping may yield in a non-passive system under some special conditions, we know that such systems are not necessarily unstable (Buerger et al, 2001). To this end, our result complements the findings by Willaert et al (2011) and Tosun and Patoglu (2020), and suggests that the upper bound of the physical damping should be considered for the stability analysis in addition to its lower bound.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Although Willaert et al (2011) and Tosun and Patoglu (2020) showed that higher physical damping may yield in a non-passive system under some special conditions, we know that such systems are not necessarily unstable (Buerger et al, 2001). To this end, our result complements the findings by Willaert et al (2011) and Tosun and Patoglu (2020), and suggests that the upper bound of the physical damping should be considered for the stability analysis in addition to its lower bound.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it is widely accepted that b eq contributes to the stability favorably (Colgate and Brown, 1994;Colgate and Schenkel, 1997;Colgate et al, 1993;Weir and Colgate, 2008), thus, only the lower bound of b eq = 0, is considered as the worst case in the earlier studies. However, Willaert et al (2011) and Tosun and Patoglu (2020) presented several examples where larger b eq may result in an active (i.e., non-passive) system under specific conditions, though the system is passive for b eq = 0. Instead of passivity, we directly investigated the stability in our analysis, and observed that our results do not indicate such a situation within the limits of the equivalent impedance considered.…”
Section: Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Representative robot and environment parameters. The device parameters were inspired by Diolaiti et al (2006), and the environment parameters by Kuchenbecker et al (2003) and Willaert et al (2011). the continuous model whose stability boundaries are similar, but not identical, to the linear hybrid and discrete model stability boundaries.…”
Section: Parameter Gain Marginmentioning
confidence: 99%
“…The classic scattering transformation or wave variables approach would lead to position drift [5] [6] and has a trade-off between stability and system performance [7] [8].…”
Section: Introductionmentioning
confidence: 99%